if s(x)=3/x+1 and t(x)=3-x/x prove that st(x)=x
and if f(x)=1/x-1, prove that f^2(x) =x+1/x+2 hence find an expression for f^3(x)
Maths c3 functions question Watch
- Thread Starter
- 11-09-2016 20:07
- 11-09-2016 20:52
For 1. you need to replace any x's in the s(x) equation with t(x), so you'd have 3/(3-x/x)+1, then simplify that down.
2. I'm not entirely sure what you mean by f^2(x) as you can test values of x and x+1/x-2 =/= (1/x-1)^2, if you mean ff(x) the its the same as above, replace any x's by f(x)Last edited by JN17; 11-09-2016 at 20:57.